Transcriptomic profiling of the extremophile eutrema salsugineum response to environmental stressors - Abou El Hassan, Diana (AUC Knowledge Fountain, 2016)
Plants are sessile organisms that are constantly exposed to a variety of abiotic and biotic environmental stresses. Some plants are known to be more tolerant to those environmental stressors than others; those are the extremophilic plants. Studying the stress response pathways in such plants is extremely important in developing transgenic crop plants with enhanced tolerance to environmental stresses. Eutrema salsugineum is an extremophilic plant that is known to be resistant to many abiotic stress factors such as drought, cold, salt, and nitrogen deficiency. Experiments were carried out in KAUST by exposing the extremophilic plant to heat stress and exogenous ABA stress. RNA sequencing was done in order to get the transcriptome profile of the plant in response to the stresses. De novo transcriptome assembly was done followed by transcript abundance quantification and normalization using Kallisto. Differential expression analaysis was done to identify the differentially expressed transcripts in response to the different treatments in the shoot and root using the R bioconductor package EdgeR. The transcripts were annotated using EggNOG. The protein coding transcripts were identified by aligning them to the nr protein database using tblastx. Functional analysis of the DE transcripts to get the enriched terms was carried out using DAVID. Trinity de novo assembly produced 49857 genes and 134493 transcripts. Out of the 134493 transcripts, 114692 (85.28%) transcripts had tblastx hits (protein coding). Thus, 19801 potentially non coding or novel transcripts have been identified. A large variety of proteins were found to be differentially expressed depending on the pair-wise comparison. The genes were mainly involved in plant heat and ABA stress, ROS signaling pathway, ROS scavenging, secondary metabolite production, and lipid transfer. Further investigation of the role of secondary metabolites such as flavonoids, and nitrogen and sulfur containing compounds in the abiotic stress response of E. salsugineum is needed since it appears to be a major mechanism used by the plant. The results of this research offer a wide variety of stress related protein in E.salsugineum. Investigation of the over-expression of some of these genes in stress sensitive plants will help in further understanding their functions and mechanisms of action.